병원 의료장비 관리실태에 관한 연구 - 유외진 (연세대학교 보건대학원, 1988)
[한글] 병원 의료장비 관리실태 및 문제점을 파악하기 위하여 전국 100병상 이상의 190개 병원을 대상으로 우편설문조사를 실시하였다. 이중 131개 병원으로부터 설문서가 회수되었으며 중요한 결과는 다음과 같다. 1.의료장비 관리체계는 병상규모별로 유의한 차이가 있으며 500병상 이상 규모의 병원은 중소규모 병원에 비해 관리체계가 비교적 잘 갖추어져 있었으며 관심도가 높았다. 2. 소유형태별로는 국공립 병원의 의료장비 관리체계가 병원보다 잘 갖추어져 있었다. 3. 소모성 의료장비 관리 분야에서는 장비 명칭 사용에 근본적인 문제가 있으며 앞으로 점차적인 교육을 통하여 이를 개선할 필요가 있는 것으로 판단되었다. 4. 의료기기 관리도 500병상규모이상의 병원이 중소규모병원 보다 잘 이루어지고 있었으나 병원 자체 정비능력의 개발과 아울러 공동관리를 위한 방안의 모색이 필요함을 알 수 있었다. 이상의 결과를 종합하면 병원의 의료장비관리분야에는 아직도 많은 문제점이 있으며 이의 개선을 위해 노력하여야 한다고 생각된다. 그러나 이 연구가 설문조사에 의해 이루어졌기 때문에 의료장비관리에 대한 심층적인 분석이 이루어지지 못하였으며 효율적인 장비관리의 해결방안을 제시하지 못한 제한점이 있다. [영문] In order to ascertain the medical equipment management status and its problems, a mailing survey was conducted among 190 hospitals nationwide, each of over 100 beds. The analysts of results collected from 131 hospitals are summarized as follows; 1. As the result of the above research, most of the hospitals-felt that there were problems in medical equipment management in many aspects, and who affirmed that there certainly was a need for improvement. Overall, it was shown that medical equipment management system was of a sub-standard level, and that there were many aspects which required improvement through collective investments. Medical equipment management system showed that there was a significant difference according to the number of beds in a hospital, i.e., the medical management system of hospitals of more than 500 beds were well organized compared to smaller hospitals. 2. In terms of ownership national or governmental hospitals have better organized medical equipment management compared to civilian or private hospitals. 3. It was of the general opinion that there was a problem in the terminology used for medical expandables and that in the future improvement was required through education. 4. It was shown that for effective management, there was a necessity for hospitals to develop further their management abilities and to study into mothods for collective management. It is necessary, hereafter, to work on a deep study to the medical equipment management system in the hospital to improve the efficiency.
보건학과/석사